Cost-effectiveness of adalimumab for early-stage Dupuytren’s disease: an economic evaluation based on a randomized controlled trial and individual-patient simulation model - Dakin, H; Rombach, I; Dritsaki, M; Gray, A; Ball, C; Lamb, SE; Nanchahal, J (British Editorial Society of Bone and Joint Surgery, 2022)
Aims: To estimate the potential cost-effectiveness of adalimumab compared with standard care alone for the treatment of early-stage Dupuytren’s disease (DD) and the value of further research from an NHS perspective. Methods: We used data from the Repurposing anti-TNF for Dupuytren’s disease (RIDD) randomized controlled trial of intranodular adalimumab injections in patients with early-stage progressive DD. RIDD found that intranodular adalimumab injections reduced nodule hardness and size in patients with early-stage DD, indicating the potential to control disease progression. A within-trial cost-utility analysis compared four adalimumab injections with no further treatment against standard care alone, taking a 12-month time horizon and using prospective data on EuroQol five-dimension five-level questionnaire (EQ-5D-5L) and resource use from the RIDD trial. We also developed a patient-level simulation model similar to a Markov model to extrapolate trial outcomes over a lifetime using data from the RIDD trial and a literature review. This also evaluated repeated courses of adalimumab each time the nodule reactivated (every three years) in patients who initially responded. Results: The within-trial economic evaluation found that adalimumab plus standard care cost £503,410 per quality-adjusted life year (QALY) gained versus standard care alone over a 12-month time horizon. The model-based extrapolation suggested that, over a lifetime, repeated courses of adalimumab could cost £14,593 (95% confidence interval £7,534 to £42,698) per QALY gained versus standard care alone. If the NHS was willing to pay £20,000/QALY gained, there is a 77% probability that adalimumab with retreatment is the best value for money. Conclusion: Repeated courses of adalimumab are likely to be a cost-effective treatment for progressive early-stage DD. The value of perfect parameter information that would eliminate all uncertainty around the parameters estimated in RIDD and the duration of quiescence was estimated to be £105 per patient or £272 million for all 2,584,411 prevalent cases in the UK.